Analysis of lightning-ionosphere interaction using simultaneous records of source current and 380 km distant electric field. (June 2017) - Azadifar, Mohammad; Li, Dongshuai; Rachidi, Farhad; Rubinstein, Marcos; Diendorfer, Gerhard; Schulz, Wolfgang; Pichler, Hannes; Rakov, Vladimir A.; Paolone, Mario; Pavanello, Davide
Abstract: We present simultaneous current and wideband electric field waveforms at 380 km associated with upward lightning flashes initiated from the Säntis Tower, Switzerland. To the best of our knowledge, the dataset presented in this study includes the first simultaneous records of lightning currents and associated fields featuring ionospheric reflections for natural upward flashes, and the longest distance at which natural upward lightning fields have been measured simultaneously with their causative currents. The intervals between the groundwave and skywave arrival times are used to estimate ionospheric reflection heights during day and night times using the so-called zero-to-zero and peak-to-peak methods. During daytime, the mean ionospheric reflection heights, obtained using the two different delay estimation approaches, are about 78 and 76 km, corresponding to the D layer. The mean reflection height at nighttime is about 90 and 89 km, corresponding to the E layer. We present a full-wave, finite-difference time-domain (FDTD) analysis of the electric field propagation including the effect of the ionospheric reflections. The FDTD simulation results are compared with the measured fields associated with upward flashes initiated from the Säntis Tower. It is found that the model reproduces reasonably well the measured waveforms and the times of arrival of the one-hop and two-hop skywaves relative to the groundwave. Highlights: Simultaneous measurements of lightning currents and corresponding fields at 380 km. Skywaves are identified and ionospheric reflection heights are estimated. FDTD simulation results are consistent with measurements for both day and night conditions.